2008
DOI: 10.1186/1749-7922-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Complicated diverticular disease of the colon, do we need to change the classical approach, a retrospective study of 110 patients in southeast England

Abstract: Background: Complicated diverticular disease of the colon imposes a serious risk to patient's life, challenge to surgeons and has cost implications for health authority. The aim of this study is to evaluate the management outcome of complicated colonic diverticular disease in a district hospital and to explore the current strategies of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
3
11
0
1
Order By: Relevance
“…The sex difference is similar to that in another Japanese study 14 . However, many Western studies of diverticular hemorrhage have indicated a female predominance or no sex difference at all 1,15,16 . At present, we do not know the precise reason for these differences.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The sex difference is similar to that in another Japanese study 14 . However, many Western studies of diverticular hemorrhage have indicated a female predominance or no sex difference at all 1,15,16 . At present, we do not know the precise reason for these differences.…”
Section: Discussionsupporting
confidence: 74%
“…at all. 1,15,16 At present, we do not know the precise reason for these differences. However racial difference actually exists, like different location of diverticular disease among races.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There was no change in the surgical management strategies and additionally there was no increase in the likelihood of subsequent reversal during the study period. This is again reflective of other studies (8,21,22).…”
Section: Discussionsupporting
confidence: 87%
“…La mayoría de los grados II requieren drenaje del absceso intraabdominal de forma percutánea, como complemento al tratamiento antibiótico. El tratamiento quirúrgico se reserva para los casos de diverticulitis complicada con peritonitis (grados III y IV de Hinchey) y, de forma electiva, para los pacientes a partir del segundo episodio y en casos de dificultad para el drenaje radioguiado 9 .…”
Section: Discussionunclassified